Evaluating social media marketing in Afghanistan’s private Universities - Safi, Abdul Qayoum; Setianti, Yanti; Sapi, Abdulmanan (Universitas Padjadjaran, 2023)
Background: Social media has become a significant part of our lives today. Students, in particular, use Internet media technologies to access information about their educational environments. Purpose: This study aimed to assess how private institutions in Afghanistan use social media for marketing purposes. Methods: The perspectives and experiences of noteworthy stakeholders in these universities were investigated using a qualitative research design by conducting in-depth interviews to explore the perceptions and experiences of key stakeholders in private universities in Afghanistan. Thematical analysis was used to examine the data gathered. Results: Social media is crucial for attaining marketing objectives and increasing brand recognition. According to the interviews, social media sites like Facebook, Twitter, Instagram, and LinkedIn are valuable tools for promoting higher education programs and interacting with prospective students. The findings also show that Facebook in Afghanistan, is the most widely used social media sites. Conclusion: Social media has become an essential marketing tool for Afghanistan’s private education institutions. Albeit poor and expensive internet access, which have significantly reduced the effectiveness of social media marketing. The importance of institutions in recognizing their target market, creating efficient social media strategies, and allocating funds wisely, are paramount in order to fulfill the goals. Despite these difficulties, participants saw social media as a valuable tool for promoting higher education programs and connecting with prospective students. Implications: Private education institutions in Afghanistan should recognize the significance of social media as an essential marketing tool despite the challenges of poor internet access and high costs and focus on understanding their target market, developing efficient social media strategies, and allocating resources effectively.